2018
DOI: 10.1002/jbm.b.34133
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial granules used for filling bone defects constitute 3D scaffolds: porosity, microarchitecture and molecular composition analyzed by microCT and Raman microspectroscopy

Abstract: Biomaterials are used in the granular form to fill small bone defects. Granules can be prepared with a grinder from trabecular bone samples or provided as synthetic biomaterials by industry. Granules occupy the 3D-space and create a macroporosity allowing invasion of vascular and bone cells when the inter-granular pores are larger than 300 µm. We compared the 3D-porosity of granule stacks obtained or prepared with nine biomaterials Osteopure , Lubboc , Bio-Oss , CopiOs , TCP Dental , TCP Dental HP , KeraOs , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…However, the manufacturer (Kasios SAS) and importer (B.IMTECH, Yongin, Korea) advertised as 99% of β-TCP. Many studies and FDA 510(k) also represented as β-TCP17575859606162636465. It was received human study level III by successful histologic and clinical result comparing Xenograft (BonePlus-xs; Integros, Adana, Turkey) in sinus lift57.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the manufacturer (Kasios SAS) and importer (B.IMTECH, Yongin, Korea) advertised as 99% of β-TCP. Many studies and FDA 510(k) also represented as β-TCP17575859606162636465. It was received human study level III by successful histologic and clinical result comparing Xenograft (BonePlus-xs; Integros, Adana, Turkey) in sinus lift57.…”
Section: Resultsmentioning
confidence: 99%
“…It was received human study level III by successful histologic and clinical result comparing Xenograft (BonePlus-xs; Integros, Adana, Turkey) in sinus lift57. Animal, in vivo , and in vitro studies for osteoconductivity5859606162636465.…”
Section: Resultsmentioning
confidence: 99%
“…The small size of the animal model necessitated that bone graft particles be morselized prior to their introduction into the tunnel. While some commercial vendors claim that at least some of the efficacy of their bone graft materials is related to particle size [ 60 ], we found that the morselized particles were effective at supporting osteoprogenitor cell attachment and new bone formation ( Figs. 1 , 2 ).…”
Section: Discussionmentioning
confidence: 91%
“…). Numerous studies have been carried out comparing the characteristics of different granular ceramics as bone filling substitutes with those of trabecular bone (Chappard et al ., ; Kerckhofs et al ., ; Arbez et al ., ). When comparing different size of granules, Arbez et al .…”
Section: Xct Characterisation Of Scaffolds and Biomaterialsmentioning
confidence: 97%
“…Numerous studies have been carried out comparing the characteristics of different granular ceramics as bone filling substitutes with those of trabecular bone (Chappard et al, 2015;Kerckhofs et al, 2016;Arbez et al, 2019). When comparing different size of granules, Arbez et al (2019) demonstrated that small granules provided scaffolds with low interconnected pores and may not be favourable for vascular invasion in situ when grafted in a bone defect, whereas the large granules (i.e., 1000-2000 µm) provided 3D scaffolds with interconnectivity well suitable for osteoconduction. XCT also allows for a 3D representation of the pore size within the scaffold (van Lenthe & Müller, 2008;Chappard et al, 2015) and to examine the time-dependent structural characteristics and the in vitro dissolution behaviour of different bioglasess (Westhauser et al, 2017).…”
Section: Xct Characterisation Of Scaffolds and Biomaterialsmentioning
confidence: 99%